International journal of intangible heritage - The National Folk Museum of Korea; Cummins, Alissandra (Seoul, Korea : The National Folk Museum of Korea, 2014)
"The International Journal of Intangible Heritage is a refereed academic and professional English language journal dedicated to promoting understanding of all aspects of intangible heritage worldwide, and to the communication of research and examples of best practice."
E-folklore and cyber-communication among Emirati youth El-Aswad, El-Sayed
Includes bibliographical references.
In English.
Keywords: Culture -- Study and teaching. Research. Cultural studies; Culture -- Periodicals; Culture property -- Periodicals -- Protection; Multiculturalism -- Periodicals